Pigmented purpuric dermatosis in two patients with common variable immunodeficiency (Swiss Medical Weekly, 2026)
Pigmented purpuric dermatosis is a benign type of chronic angiodermatitis prevalent in the general population, presenting with a relapsing-remitting course, with predominantly idiopathic aetiology and both humoral and cell-mediated immune pathogenesis.We report to our knowledge the first two cases of clinical association between such dermal capillaritis and the most clinically heterogeneous form of primary immunodeficiency: common variable immunodeficiency. Furthermore, in the light of already suggested triggers and pathophysiological mechanisms correlating pigmented purpuric dermatosis with various forms of secondary immunodeficiency, we complete our case descriptions by the proposal of a new putative aetiopathogenic actor that would likely account for the occurrence of the clinical association described.